2017
DOI: 10.1021/acs.langmuir.7b03418
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Nanoparticles in Entangled Polymer Solutions

Abstract: The mean square displacement ⟨r⟩ of nanoparticle probes dispersed in simple isotropic liquids and in polymer solutions is interrogated using fluorescence correlation spectroscopy and single-particle tracking (SPT) experiments. Probe dynamics in different regimes of particle diameter (d), relative to characteristic polymer length scales, including the correlation length (ξ), the entanglement mesh size (a), and the radius of gyration (R), are investigated. In simple fluids and for polymer solutions in which d ≫ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 81 publications
(154 reference statements)
7
49
1
Order By: Relevance
“…This size difference, which correlates to a ~6x difference in DNA coil radius, is of principal importance, as the degree of crowding-induced subdiffusion has been shown to depend directly on the ratio of particle or polymer radius to the correlation length of the crowding network. 50,51 In particular, for colloids diffusing in actin networks, subdiffusion was only apparent when the colloid radius a was comparable to the mesh size of the actin network ξ A , with α decreasing linearly with increasing ratios a:ξ A . 50 In our experiments, the DNA coil radius is ~½R coil ≈ 0.6 -0.8 μm.…”
Section: Resultsmentioning
confidence: 99%
“…This size difference, which correlates to a ~6x difference in DNA coil radius, is of principal importance, as the degree of crowding-induced subdiffusion has been shown to depend directly on the ratio of particle or polymer radius to the correlation length of the crowding network. 50,51 In particular, for colloids diffusing in actin networks, subdiffusion was only apparent when the colloid radius a was comparable to the mesh size of the actin network ξ A , with α decreasing linearly with increasing ratios a:ξ A . 50 In our experiments, the DNA coil radius is ~½R coil ≈ 0.6 -0.8 μm.…”
Section: Resultsmentioning
confidence: 99%
“…This size difference is of principal importance as the degree of crowdinginduced subdiffusion has been shown to depend directly on the ratio of particle or polymer radius to the correlation length of the crowding network. 47,48 In particular, for colloids diffusing in actin networks, subdiffusion was only apparent when the colloid radius a was comparable to the mesh size of the actin network , with α decreasing linearly with increasing ratios a:. 47 In our experiments, the DNA coil radius is ~½Rcoil  0.6 -0.8 μm, whereas the predicted mesh sizes for the actin and microtubule networks are   0.4 μm and   0.9 μm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of trapping times results in subdiffusion over many decades in time. 4,7,47,48 Such caging and hopping behavior should also manifest itself as large heterogeneities in transport measured for different molecules in different regions of the network. 4,47 Within this framework, more extreme subdiffusion (smaller α), resulting from more efficient caging, should be coupled with larger heterogeneities in transport.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, an exceptional degree of dispersion of the silica in the polymer and high degree of order in both thin film and bulk forms was achieved [18]. For matrix-free model systems [34,35] it was observed that NPs diffuse similarly to a polymer solution [36][37][38], while chains diffuse faster than NPs [39]. Ionic interactions are also included in the case of ionomers in which the morphology and phase behavior depend on the electrostatic strength [40][41][42].…”
Section: Introductionmentioning
confidence: 99%